Formulasi Dan Uji Aktivitas Antibakteri Sabun Kertas Virgin Coconut Oil (VCO) Dengan Variasi Gliserin Sebagai Plasticizer Terhadap Staphylococcus Aureus - Apriani, Aida; Dewi, Resmila; Sidiq, Teuku Sultan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Virgin Coconut Oil (VCO) contains medium-chain saturated fatty acids (MCFA), particularly lauric acid, which is known for its antibacterial properties. VCO has the potential to be formulated into a practical and hygienic paper soap dosage form. In paper soap formulation, glycerin acts as a plasticizer that affects the physical properties of the preparation, but its effect on antibacterial activity has not been widely explored. Objective: This study aimed to formulate VCO paper soap with variations in glycerin concentration and to analyze its antibacterial activity against Staphylococcus aureus. Methods: This experimental research formulated four paper soap formulas with variations in glycerin concentration: 0% (F1), 10% (F2), 15% (F3), and 20% (F4). The preparations were evaluated through organoleptic tests, pH tests, foam height tests, and free alkali tests. Antibacterial activity was tested against Staphylococcus aureus using the disk diffusion method (Kirby-Bauer) with a positive control (commercial paper soap) and a negative control (aquadest). Results: The evaluation results showed that all formulas met the physico-chemical quality standards for soap. Formula 3 (15% glycerin) was the best preparation based on overall evaluation. The antibacterial test showed that all four VCO paper soap formulas (F1-F4) had moderate antibacterial activity against Staphylococcus aureus with inhibition zone diameters that were not statistically significantly different. The negative control showed no activity, while the positive control showed strong antibacterial activity. Conclusion: It was concluded that VCO paper soap was successfully formulated and exhibited moderate antibacterial activity against Staphylococcus aureus. Variations in glycerin concentration (0-20%) did not significantly affect the antibacterial activity, which is presumed to be more influenced by the lauric acid content in VCO.